USING LISTENING DIARY TO TRACK NON-ENGLISH-MAJORED STUDENTS’ ONLINE LEARNING ON LEARNING MANAGEMENT SYSTEM - Hai, Ngo Thi Minh; Huyen, Nguyen Thi (VNU Journal of Foreign Studies; Vol 38 No 5, 2022)
This study was carried out to examine if second-year non-English-majored students’ online listening learning in learning management system (LMS) can be improved through using listening diary and to investigate students’ attitudes towards this method. The action research used survey questionnaires with 53 students, group interviews with 30 students, an analysis of students’ 53 listening diaries in 10 weeks and teachers’ diaries at a Vietnamese university. The findings of the study showed that listening diary could be utilized as a pedagogical tool to help teachers understand and control students’ online listening activities. Besides, the data revealed that listening diary gave students a chance to identify their problems, encouraged them to be active in finding appropriate strategies for their listening as well as contributed to raising students’ interest in learning listening. It is recommended that this method should be widely recognized and applied to non-English-majored students to enhance the effectiveness of online learning.